Runoff of small rocky headwater catchments: Field observations and hydrological modeling. Issue 10 (21st October 2016) - Gregoretti, C.; Degetto, M.; Bernard, M.; Crucil, G.; Pimazzoni, A.; De Vido, G.; Berti, M.; Simoni, A.; Lanzoni, S.
Abstract: In dolomitic headwater catchments, intense rainstorms of short duration produce runoff discharges that often trigger debris flows on the scree slopes at the base of rock cliffs. In order to measure these discharges, we placed a measuring facility at the outlet (elevation 1770 m a.s.l.) of a small, rocky headwater catchment (area ∼0.032 km 2, average slope ∼320%) located in the Venetian Dolomites (North Eastern Italian Alps). The facility consists of an approximately rectangular basin, ending with a sharp‐crested weir. Six runoff events were recorded in the period 2011–2014, providing a unique opportunity for characterizing the hydrological response of the catchment. The measured hydrographs display impulsive shapes, with an abrupt raise up to the peak, followed by a rapidly decreasing tail, until a nearly constant plateau is eventually reached. This behavior can be simulated by means of a distributed hydrological model if the excess rainfall is determined accurately. We show that using the Soil Conservation Service Curve‐Number (SCS‐CN) method and assuming a constant routing velocity invariably results in an underestimated peak flow and a delayed peak time. A satisfactory prediction of the impulsive hydrograph shape, including peak value and timing, is obtained only by combining the SCS‐CN procedure with a simplified version of the Horton equation, and simulating runoff routing along the channel network through a matched diffusivity kinematic wave model. The robustness of the proposed methodology is tested through a comparison between simulated and observed timings of runoff or debris flow occurrence in two neighboring alpine basins. Key Points: Hydrological response to convective rainfalls in headwater rocky catchments is impulsive and mainly ruled by excess infiltration Combining SCS‐CN method for estimating excess rainfall and constant velocity for routing, the observed hydrographs cannot be reproduced Observed peaked hydrographs need a simplified Hortonian equation and the Muskingum‐Cunge scheme along network to be simulated